Анализа на митохондријална ДНК (мтДНК) од биолошки материјал во форензичките испитувања - Јанкова Ајановска, Рената (Медицински факултет, УКИМ, Скопје, 2015)
Mitochondrial DNA (mtDNA) is a small circular molecule whose caracteristics such as maternal inheritance, high copy number, lack of recombination and accumulation of polymorphism throughout the control region are widely used for forensic analysis. Human mtDNA was first sequenched in 1981 in Frederick Sanger’s laboratory in Cambridge, England. In 1999 the sequence was re-sequnced and such as is used as a reference sequence for mtDNA analysis. This sequence is reffered to as reviser Cambridge Reference Sequence (rCRS). Analysis of mtDNA hypervariable regions especially the most polimorphic ones such as HV1 and HV2 are used in many forensic laboratories worldwide for solving foresic cases where the amount of extracted DNA is very small, or where lack of reference samples for comparison asks for inclusion of additional DNA markers such as mtDNA. Population database plays an important role in estimating the expected frequency of mtDNA haplotypes that are observed in analysed sample which match with reference sample. For this reason a laboratory working with DNA or mtDNA should have its own data base from the population in the country the laboratory works. In this PhD thesis a total of 444 individuals representing three different ethnic groups (albanians, turks and romanies) in the Republic of Macedonia were sequenced in the mitochondrial DNA control region. All samples were detrmined for haplogroups according to common mutations in the mtDNA control region. The mtDNA haplogroup composition differed between the three groups. Our results showed relatively high frequencies of haplogroup H12 in albanians (8.78%) and less in turks (3.33%), while haplogroups M5a1 and H7a1a were dominant in romanies (13.7% and 10%, respectively) but were rare in the former two. This highlights the importance of regional sampling for forensic mtDNA databasing purposes. This population data will be available on EMPOP under accession numbers EMP00644 (albanians), EMP00645 (romanies) and EMP00646 (turks). While working on a PhD thesis two forensic cases were solved with implementation of mtDNA analysis. One case was identification of putrefied body and the other was testing for sister-brother relationship.
Докторска дисертација одбранета во 2015 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Алексеј Дума.
Keywords: mtDNA, EMPOP, haplogroups, albanian, turks, romanies, forensic genetics